Adoption of Traditional Agroforestry in Kangra Valley of Himachal Himalayas - Punam, .; Atul, .; Rameshwar, . (Indian Journal of Agroforestry, 2020)
Traditional agroforestry systems are based largely on indigenous knowledge and species, which are part of the cultural traditions of the local community. Agroforestry systems with their multi-storey vegetation structure and diverse plant composition have been maintained as a part of rural livelihood. In order to understand the status and complexity of traditional agroforestry system, this study was undertaken to establish, how many, and what type of species the farmers adopt. The phyto-sociological data collected were analyzed for the Kangra valley from lower foothills to mid-hill areas. With the increase in the altitude there is an increase in the integration of the tree component in the farmers fields; the mean prevalence of trees at farmers field increased from 47% in lower foothills to 67% in mid hills. The species-specific adoption by farmers of Kangra valley showed different patterns when data were analyzed at a cumulative and at a micro-zonal level. Farmers primarily focused on adoption of timber and horticulture trees in foothills and fuelwood and fodder species in mid hills.